Successful endovascular embolization of the common hepatic artery for pseudoaneurysm associated with pancreatic fistula after liver transplantation: a case report - Kazuki Sasaki; Tadafumi Asaoka; Shogo Kobayashi; Yoshifumi Iwagami; Daisaku Yamada; Yoshito Tomimaru; Takehiro Noda; Hiroshi Wada; Kunihito Gotoh; Hidenori Takahashi; Noboru Maeda; Yasushi Kimura; et al. (Surgical Case Reports)
Abstract Background After orthotopic liver transplantation (OLT), complications such as hepatic artery stenosis, thrombosis, and bleeding are possible. Hepatic artery pseudoaneurysms (HAP) are prone to rupture, rupture hemorrhage, and increased mortality risk. Endovascular treatment of HAP may result in recurrence, even after successful embolization with thrombin. Formation of a HAP in the common hepatic artery (CHA) is challenging because the CHA is the only artery in the liver graft after OLT. Therefore, CHA embolization in HAP is not an initial option. We report a case of HAP at the CHA after OLT that was treated with endovascular therapy, resulting in the occlusion of the CHA with coil embolization, achieving a radical cure. Case presentation A 59-year-old man with decompensated hepatitis C virus cirrhosis underwent deceased donor whole-liver transplantation after graft failure of a living donor liver transplantation. After the second transplantation, the patient developed infectious narrow-necked HAP at the CHA associated with postoperative pancreatic fistula. Repeated transcatheter arterial embolization with thrombin and n-butyl-2-cyanoacrylate was unsuccessful, as confirmed by postprocedure angiography, which revealed recanalization and regrowth of the HAP. Eight months after the first transcatheter arterial embolization, the patient presented with a chief complaint of abdominal pain due to an enlarged HAP. Angiography of the superior mesenteric artery (SMA) revealed a collateral bypass around the bile duct from the SMA to the liver graft. Coil embolization of the HAP in the CHA completely occluded the HAP without complications. More than 2 years after coil embolization, the liver graft function test results remained within normal limits without HAP recurrence. Conclusions HAP at the CHA after liver transplantation can be fatal if ruptured. Because the liver is a highly angiogenic organ, even if initial treatment is not successful, radical treatment to occlude the CHA with HAP is possible if sufficient collateral vessels are developed.